Fictional Characters in Literary Theory — A Short History - Marcus HARTNER (E-REA, 2024)
This contribution to the special issue on “The Persistence of Character” provides a brief history of approaches to fictional characters in literary studies, from the emergence of structuralism to current explorations of fictional beings in the context of 4E cognition. By sketching the different stages in the development of character theory since the mid-twentieth century the article shows that the influential (post)structuralist conception of characters as signs, symbols, and (plot) functions, which still occupies a key position in literary scholarship today, fails to do justice to the fascination literary figures frequently exert on readers. With a particular focus on the field of narratology, the article traces the ways in which this “antihumanist” (Felski) conception of fictional characters has been challenged over the past decades. Furthermore, it demonstrates how new theoretical developments in this field tend to be closely intertwined with overarching developments in literary theory in general.